Pengembangan getuk kacang tolo sebagai makanan selingan alternatif kaya serat - Fenthy Marlina Safitri; Dwi Ratna Ningsih; Elza Ismail; Waluyo Waluyo (Alma Ata University Press, 2016)
ABSTRACTBackground: Getuk is traditional food that is familiar in all age group. However, information about nutrient content and bioactive substance of getuk are not widely available. Cowpea contains phytic acid, protein and high of calcium gives many beneficial for our body. Phytic acid may decrease cholesterol level in serum and blood glucose level because its role as dietary fiber. Protein and calcium are macro nutrient which have important roles to build our body.Objectives: This research aimed to know the differences in qualitative and quantitative sensory characteristic, phytic acid, protein, and calcium levels of getuk kacang tolo with variations of cowpea.Methods: This study was quasi experimental research with simple random design using 4 treatments, 2 replicates, and 2 experiment units. Getuk were made from cassava and substituted with cowpea with different concentration, e.g. 0% as control, 25%, 50% and 75%. Sensory characteristics were assessed qualitatively by description and quantitatively by using 25 panelists. Quantitative sensory data were analyzed using statistical tests of Kruskal Wallis continued with Mann-Whitney analysis if there were a difference result. Phytic acid, protein, and calcium levels were analyzed using statistical test Anova continued with Tukey test if there were a difference result.Results: Substitution of cowpea made getuk became darker, the texture became less chewiness, whereas aroma and flavor still the same with the control. Panelist preferred color, texture, aroma, and flavor of getuk with concentration of cowpea substitution 50%, 75%, 25%, and 50%, respectively. Phytic acid levels in 100 g material with the substitution of cowpea 0%, 25%, 50% and 75% were 12.5 mg; 42.8 mg; 57.9 mg; 69.2 mg respectively. Protein level on 0%, 25%, 50% and 75% were 1.16 g; 2.96 g; 4.56 g; 6.13 g also calcium level on 0%, 25%, 50% and 75% were 237.2 mg; 388.1mg; 596.27mg; 736.57mg.Conclusions: Different variations of cowpea substitution in producing getuk kacang tolo had the impact on sensory characteristics, phytic acid, calcium, and protein levels.KEYWORDS: cowpea, getuk, sensory characteristic, phytic acid, calcium, proteinABSTRAKLatar belakang: Getuk merupakan makanan tradisional yang familiar di semua golongan usia, namun kandungan zat gizi dan zat bioaktif pada getuk belum tersedia. Kacang tolo mengandung asam fitat, protein dan kalsium yang bermanfaat bagi tubuh. Asam fitat dapat menurunkan kadar kolesterol dan mengurangi kadar glukosa darah karena termasuk ke dalam serat pangan. Protein dan kalsium memiliki peran penting dalam tubuh yang merupakan zat gizi makro yang bermanfaat untuk membangun tubuh.Tujuan: Mengetahui perbedaan sifat sensoris kualitatif dan kuantitatif, kadar asam fitat, protein dan kalsium pada getuk kacang tolo dengan variasi pencampuran kacang tolo.Metode: Jenis penelitian ini adalah eksperimen semu dengan rancangan acak sederhana (RAS) menggunakan 4 perlakuan, 2 kali ulangan, dan 2 unit percobaan. Sampel penelitian adalah getuk kacang tolo dengan pencampuran kacang tolo 0% sebagai kontrol, 25%, 50% dan 75%. Sifat sensoris dianalisissecara kualitatif melalui deskripsi dan kuantitatif menggunakan 25 panelis. Analisis data sifat sensoris menggunakan uji statistik Kruskal Wallis dilanjutkan Mann-Whitney jika ada perbedaan. Kadar asam fitat, protein dan kalsium dianalisis dengan Anova dilanjutkan uji Tukey jika ada perbedaan.Hasil: Pencampuran kacang tolo pada getuk kacang tolo menghasilkan warna semakin kecokelatan, tekstur semakin tidak kenyal, aroma dan rasa sama dengan kontrol. Warna getuk kacang tolo dengan pencampuran kacang tolo 50%, tekstur getuk dengan pencampuran kacang tolo 75%, aroma getukdengan pencampuran kacang tolo 25%, dan rasa dengan pencampuran kacang tolo 50% dinilai paling disukai panelis. Kadar asam fi tat dalam 100 g getuk dengan pencampuran kacang tolo 0%, 25%, 50% dan 75% berturut-turut adalah 12,5 mg; 42,8 mg; 57,9 mg; 69,2 mg. Kadar protein 0%, 25%, 50% dan 75% sebanyak 1,16 g; 2,96 g; 4,56 g; 6,13 g dan kadar kalsium 237,2 mg; 388,1 mg; 596,27 mg; 736,57 mg berturut-turut.Kesimpulan: Variasi pencampuran kacang tolo pada pembuatan getuk kacang tolo berpengaruh terhadap sifat fisik, organoleptik, dan kadar asam fitat.KATA KUNCI: kacang tolo, getuk, sifat sensoris, kadar asam fitat, protein, kalsium